Theologian of Sin and Grace The Process of Radicalization in the Theology of Matthias Flacius Illyricus (Volume 225, Edition 1) - Ilic, Luka (2014)
The Croatian-born Matthias Flacius Illyricus (1520-1575) was a Lutheran theologian and reformer who spent most of his adult life in the German-speaking territories of the Holy Roman Empire, playing an important role within the Evangelical churches and in the confessionalization of his day. Luka Ili? establishes that Flacius' theology became increasingly radicalized with time and examines aspects of this process through following two parallel tracks. One trajectory focuses on the development of Flacius' theological thought, while the other one discusses the pivotal influences and major turning points in his life, such as being exiled from different cities. Although Flacius did enjoy some measure of success and even attracted a considerable number of followers for shorter periods of time, his radicalized theology ultimately led to his public downfall and marred his legacy. Flacius' relationships with the most important Wittenberg figures, Luther and Melanchthon, are also explored, along with the vast personal and professional networks Flacius built up in imperial cities, all of which shaped his theological development. One of the dominant claims is that Flacius' understanding of original sin and of grace were the lynchpin for much of his opus. At the same time, the findings demonstrate that Flacius was a multifaceted individual with interest and competences in a number of different academic fields.